Stimulation of incretin secreting cells - Pais, Ramona (Ther Adv Endocrinol Metab, 2016)
The incretin hormones glucose-dependent insulinotropic polypeptide (GIP) and glucagon like peptide-1 (GLP-1) are secreted from enteroendocrine cells in the gut and regulate physiological and homeostatic functions related to glucose control, metabolism and food intake. This review provides a systematic summary of the molecular mechanisms underlying secretion from incretin cells, and an understanding of how they sense and interact with lumen and vascular factors and the enteric nervous system through transporters and G-protein coupled receptors (GPCRs) present on their surface to ultimately culminate in hormone release. Some of the molecules described below such as sodium coupled glucose transporter 1 (SGLT1), G-protein coupled receptor (GPR) 119 and GPR40 are targets of novel therapeutics designed to enhance endogenous gut hormone release. Synthetic ligands at these receptors aimed at treating obesity and type 2 diabetes are currently under investigation.